2021
DOI: 10.3390/ani11030838
|View full text |Cite
|
Sign up to set email alerts
|

Diet Transition from High-Forage to High-Concentrate Alters Rumen Bacterial Community Composition, Epithelial Transcriptomes and Ruminal Fermentation Parameters in Dairy Cows

Abstract: Effects of changing diet on rumen fermentation parameters, bacterial community composition, and transcriptome profiles were determined in three rumen-cannulated Holstein Friesian cows using a 3 × 4 cross-over design. Treatments include HF-1 (first high-forage diet), HC-1 (first high-concentrate diet), HC-2 (succeeding high-concentrate diet), and HF-2 (second high-forage diet as a recovery period). Animal diets contained Klein grass and concentrate at ratios of 8:2, 2:8, 2:8, and 8:2 (two weeks each), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 134 publications
5
26
1
Order By: Relevance
“…Ruminal pH was found to be steady between 6.3 and 6.6, and ruminal temperature was found to be between 38.8 and 39.3 °C. However, Ramos et al [ 36 ] discovered that diets high in concentrate typically resulted in a significant decrease in ruminal pH, a decreased digestion rate, and decreased cellulolytic bacteria activity. Ruminal pH and its daily fluctuations can be considered a major factor in the occurrence of SARA and the regulation of microbial activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruminal pH was found to be steady between 6.3 and 6.6, and ruminal temperature was found to be between 38.8 and 39.3 °C. However, Ramos et al [ 36 ] discovered that diets high in concentrate typically resulted in a significant decrease in ruminal pH, a decreased digestion rate, and decreased cellulolytic bacteria activity. Ruminal pH and its daily fluctuations can be considered a major factor in the occurrence of SARA and the regulation of microbial activity.…”
Section: Resultsmentioning
confidence: 99%
“…The greater concentration of ruminal NH 3 -N in the high-concentrate diet was attributed to the dynamic equilibrium between NH 3 -N production and use by rumen bacteria. The presence of high levels of NH 3 -N in the rumen shows that animals may be receiving adequate accessible nitrogen content from dietary intake, most likely as a result of the high concentrate content of the cow diet [ 36 ]. However, the addition of LY significantly enhanced the NH 3 -N content ( p < 0.05), contrary to the findings of Li et al [ 33 ], who showed that the addition of S. cerevisiae had no effect on the NH 3 -N concentration in the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…This supports the results of the present study, considering the relative abundance of P. ruminicola during the high-concentrate diet period. Similarly, the high abundance of P. jejuni in CON may have been due to its ability to ferment glucose and its cell function as a saccharolytic bacteria [27,78]. Rumen microbes have a unique ability to convert carbohydrates to shortchain fatty acids at a rate that exceeds the absorptive, buffering, and outflow capacity of the rumen, which causes a sudden decrease in ruminal pH [6].…”
Section: Discussionmentioning
confidence: 99%
“…Each fluid sample was strained through four layers of surgical gauze and pooled in an amber bottle with an oxygen-free headspace, which was subsequently capped after collection. The collected samples were maintained at 39 • C and immediately transported to the laboratory [27]. For each treatment, 70 mL of rumen fluid was dispensed under a stream of CO 2 into a serum bottle containing 0.5 g of the treatment buffer and 2.5 g dry matter (DM) of ground corn grain, which served as the substrate [26].…”
Section: Rumen Fluid Collection and Analyses For In Vitro Rumen Fermentation And Buffering Capacitymentioning
confidence: 99%
“…The rumen and its health are the key to improving production efficiency in beef cattle farming [ 10 ]. The rumen is a complex microbial environment, hosting numerous strains of bacteria and microorganisms which coexist and perform at best only in specific and stable environmental conditions [ 11 ]. The main factors influencing the growth and activity of ruminal microbiota are pH (average values of 5.8–6), buffering capacity, osmotic pressure and redox potential.…”
Section: Introductionmentioning
confidence: 99%